Land and 'space' for regulating artisanal mining in Cambodia: Visualizing an environmental governance conundrum in contested territory. (July 2016) - Spiegel, Samuel
Highlights: Study examines how land use governance practices prioritise large-scale concessions over artisanal mining. Cambodia signed new global environmental treaty calling for "formalizing" artisanal gold mining. Study explores map of mining concessions in Kratie Province, re-conceptualising treaty's implications. Analysis illustrates competing visions of "productive space" and competing policy mandates. The article highlights dialectical relations between physical and political space. Abstract: Globally, land use competition in mining areas is coming under increased scrutiny, leading to critical debates about inter-related physical and political "spaces" for environmental governance. By signing a global treaty called the Minamata Convention on Mercury, governments worldwide have conveyed a commitment to formalizing or regulating informal artisanal gold mining as part of an environmental governance strategy. Drawing on a case study of disputed gold mining territory in Kratie Province, Cambodia, this article examines how commitment to the Minamata Convention presents a conundrum given the government's prioritization of larger-scale concessions in land use policy. In most mineral-rich regions of Kratie and other provinces, mineral exploration and/or mining rights – and other kinds of resource concessions – have already been granted to established companies and powerful actors, leaving ambiguous physical and political space for licensing artisanal mining. The article explores contested representations of mining as found in provincial government maps and civil society groups' cartoon illustrations, unpacking how competing mandates in the mining sector have created dilemmas for regional environmental governance as complex land-use conflicts between artisanal miners and larger companies have unfolded. Diverse competing claims to resources in Kratie illustrate the need to move beyond framings of the Minamata Convention as a technical implementation challenge in order to carefully appreciate the power dynamics inherent in divergent ways of visualizing "productive space" in mining regions. Contributing to recent scholarship in this journal on contested land use governance in Cambodia, the article calls for unpacking complexities of formally "making space" for artisanal mining in contested territory. At a wider conceptual level, the analysis highlights the importance of sensitively challenging common de-territorialized depictions of land use formalization that oversimplify the dialectical and contextually idiosyncratic interplays between political and physical space.